Penerapan Model Pembelajaran Mind Mapping Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Mata Pelajaran PKn - Budaya Budaya (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The research objective was to describe the application of the Mind Mapping model to improve students' creative thinking skills in Civics subjects at SMA Muhammadiyah Kalosi, Enrekang Regency. This type of research is a classroom action research using qualitative descriptive methods. The results showed that the increase in students 'creative thinking skills was marked by the increase in the average score of students' creative thinking abilities, namely from Cycle I of 51.60% (sufficient category) to Cycle II to 70.65% (Good category). It can be concluded that the application of the Mind Mapping model can improve students' creative thinking skills in Civics subjects at SMA Muhammaduiyah Kalosi, Kabupaten Enrekang.